Kesan energi Selawat Nabi berdasarkan perubahan warna aura - Kurniawan Yohan, Yohan Hishamuddin, Nik Abd. Rahman Nik Mutasim, Inayatullah Othman, Yusuff Nur Azuki, Musa Nik Yusri (Universiti Pendidikan Sultan Idris, 2016)
Kesan energi Selawat Nabi berdasarkan perubahan warna aura by Kurniawan Yohan, Yohan Hishamuddin, Nik Abd. Rahman Nik Mutasim, Inayatullah Othman, Yusuff Nur Azuki, Musa Nik Yusri,